Genomewide association analysis of salt tolerance in soybean [Glycine max (L.) Merr.]. (20th August 2018) - Huang, Lei; Zeng, Ailan; Chen, Pengyin; Wu, Chengjun; Wang, Dechun; Wen, Zixiang
Abstract: Salinity is a common abiotic stress causing soybean [ Glycine max (L.) Merr.] yield loss worldwide. The use of tolerant cultivars is an effective and economic approach to coping with this stress. Towards this, research is needed to identify salt‐tolerant germplasm and better understand the genetic and molecular basis of salt tolerance in soybean. The objectives of this study were to identify salt‐tolerant genotypes, to search for single‐nucleotide polymorphisms (SNPs) and QTLs associated with salt tolerance. A total of 192 diverse soybean lines and cultivars were screened for salt tolerance in the glasshouse based on visual leaf scorch scores after 15–18 days of 120 mM NaCl stress. These genotypes were further genotyped using the SoySNP50K iSelect BeadChip. Genomewide association mapping showed that 62 SNP markers representing six genomic regions on chromosomes (Chr.) 2, 3, 5, 6, 8 and 18, respectively, were significantly associated with salt tolerance ( p  < 0.001). A total of 52 SNP markers on Chr. 3 are mapped at or near the major salt tolerance QTL previously identified in S‐100 (Lee et al., 2014). Three SNPs on Chr. 18 map near the salt tolerance QTL previously identified in Nannong1138‐2 (Chen, Cui, Fu, Gai, & Yu, 2008). The other significant SNPs represent four putative minor QTLs for salt tolerance, newly identified in this study. The results above lay the foundation for fine mapping, cloning and molecular breeding for soybean salt tolerance.